English versus Zambian Languages: Exploring some Similarities and Differences with their Implication on the Teaching of Literacy and Language in Primary Schools (British Journal of Multidisciplinary and Advanced Studies, 2023)
This desk study aimed at comparing English and selected Zambian Languages with a view of identifying some similarities and differences. Data was collected through author introspection and document analysis of existing literature. Publications in English and some Zambian Languages were collected from international databases such JSTOR, Cambridge Journals Online, and Palgrave Macmillan Journals. Searches for literature was extended to Google Scholar, Institutional Repository and visited the University of Zambia library in person. The documents  collected were subjected to content analysis where key words, concepts and themes were picked and compared. Findings of the study revealed that English Language has an opaque orthography as there is no grapheme-phoneme correspondence while Zambian Languages have a transparent orthography where each grapheme correspond to individual sounds and that the number of graphemes is almost equal to phonemes. Literacy and language instruction would be much easier for learners in a transparent orthography than opaque. English has certain parts of speech such as articles (determiners) which are not there in Zambian Languages. Unlike English, vowel length is distinctive in all Zambian language. English and Zambian languages use alphabetic writing system with about 93% shared symbols or graphemes. These similarities and variations imply that pedagogically, if learners learn letter knowledge and decoding in a Zambian language, they will transfer such knowledge to English or any other alphabetic language and vice versa. Conversely, in areas where there are differences, literacy and language learners will face difficulties. The study recommended that teachers in early grade classes should understand the variation of English and selected Zambian languages well in their regions to guide learners in schools.